Role of Epstein–Barr Virus in the Pathogenesis of Head and Neck Cancers and Its Potential as an Immunotherapeutic Target - Fernandes, Queenie; Merhi, Maysaloun; Raza, Afsheen; Inchakalody, Varghese Philipose; Abdelouahab, Nassima; Zar Gul, Abdul Rehman; Uddin, Shahab; Dermime, Said (Frontiers in Oncology, 2018)
The role of Epstein-Barr virus (EBV) infection in the development and progression of tumor cells has been described in various cancers. Etiologically, EBV is a causative agent in certain variants of head and neck cancers such as nasopharyngeal cancer (NPC). Proteins expressed by the EVB genome are involved in invoking and perpetuating the oncogenic properties of the virus. However, these protein products were also identified as important targets for therapeutic research in the past decades, particularly within the context of immunotherapy. The Adoptive transfer of EBV-targeted T-cells as well as the development of EBV vaccines has opened newer lines of research to conceptualize novel therapeutic approaches towards the disease. This review addresses the most important aspects of the association of EBV with head and neck cancers from an immunological perspective. It also aims to highlight the current and future prospects of enhanced EBV-targeted immunotherapies.